TRANSFORMASI DIGITALISASI PERPAJAKAN: TRANSISI DARI DJP ONLINE KE CORETAX PADA INSPEKTORAT DAERAH KABUPATEN BLORA - Nawawi Isnan; Devi Maya Sofa (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
The digital transformation of taxation is a strategic step taken by the Indonesian government to improve administrative efficiency, data accuracy, and fiscal accountability. One of the main implementations of this policy is the implementation of the Coretax Administration System (Coretax), which replaces the previous system, DJP Online. Coretax is designed as an integrated core taxation system capable of integrating various tax reporting and validation applications into a single, standardized national database. This study aims to analyze the transition process from DJP Online to Coretax and assess its impact on tax administration performance at the Blora Regency Inspectorate, as a representative of local government agencies adapting to the new digital-based system. The research method used is descriptive qualitative, with data collection techniques through semi-structured interviews with tax administration staff and observations of tax reporting documents before and after the implementation of Coretax. The analysis was conducted by examining changes in work procedures, obstacles that emerged during implementation, and employee perceptions of the system's effectiveness. To ensure validity, triangulation of sources and methods was conducted so that the research results describe field conditions objectively and comprehensively. The study results showed that the transition period was marked by various obstacles, such as system errors, login difficulties, data matching, and limited employee understanding of the new workflow. These conditions led to increased workloads and reporting delays in the initial implementation phase. However, Coretax has proven capable of improving reporting accuracy through automated data validation, information integration, and reduced input errors. The study concluded that the benefits of digitalization have begun to be seen. However, the system's effectiveness still needs to be strengthened through increased human resource competency, more equitable digital infrastructure support at the regional level, and ongoing support from the central tax authority.